Business Process Modeling Notation Second International Workshop, BPMN 2010, Potsdam, Germany, October 13-14, 2010. Proceedings - Mendling, Jan.; Weidlich, Matthias; Weske, Mathias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the second workshop on Business Process Modeling Notation, BPMN 2010, held in Potsdam, Germany, in October 2010. The 6 research papers presented were carefully reviewed and selected from 16 submissions. In addition, 3 short papers and the extended abstracts of 3 invited talks are included. The BPMN workshop series provides a forum for academics and practitioners who share an interest in business process modeling using the Business Process Modeling Notation, which is seen by many as the de facto standard for business process modeling. BPMN promises to bridge business and IT and brings process design and implementation closer together.
Keywords: Economics; Software engineering; Information systems; Management information systems; Economics/Management Science; Business Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl.Internet).; Software Engineering